Ultrastructural Study of Acanthamoeba polyphaga Trophozoites and Cysts Treated In Vitro with Cationic Carbosilane Dendrimers - Irene Heredero-Bermejo; Tania Martín-Pérez; José Luis Copa-Patiño; Rafael Gómez; Francisco Javier de la Mata; Juan Soliveri; Jorge Pérez-Serrano (MDPI AG, 2020)
Cationic carbosilane dendrimers are branched molecules with antimicrobial properties. Their activity has been tested against Acanthamoeba polyphaga, a causative agent of Acanthamoeba keratitis, a severe ocular disease in humans. A. polyphaga trophozoites and cysts were exposed to different noncytotoxic cationic carbosilane dendrimers with proven antiamoebic activity. The effects of treatment on cell surface and cell ultrastructure were examined by scanning and transmission electron microscopy, respectively. Two of the dendrimers tested induced dramatic alterations of cellular ultrastructure in both trophozoites and cysts, including vacuolization, depletion of cytoplasmic contents, and reduced cell size. Additionally, we observed severe alterations of the plasma membrane with membrane blebbing in trophozoites and disruption in cysts. These alterations were also observed with chlorhexidine, a drug used for treatment of Acanthamoeba keratitis. Our results support that these compounds may target membranes, and their action is critical for parasite integrity.